2020
DOI: 10.1111/poms.13110
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries of Focus and Volume: An Empirical Study in Neonatal Intensive Care

Abstract: Our study contributes to the scholarly debate whether organizational units should have a narrow focus and admit a homogeneous patient cluster or whether they should admit a pool of patient clusters. We investigate whether the benefits of increased volume through pooling patients outweigh the disadvantages of increased heterogeneity and pursue our analysis in the context of neonatal care. Our empirical studies relies on 4020 patient episodes collected in 18 German neonatal intensive care units and we distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 44 publications
2
13
1
Order By: Relevance
“…Our results are not consistent with the recent study by Miedaner and Sülz [18], which found negative effects from focus in neonatal intensive care. A possible explanation of the incongruent results would be that patient characteristics moderate the impact of focus on performance.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results are not consistent with the recent study by Miedaner and Sülz [18], which found negative effects from focus in neonatal intensive care. A possible explanation of the incongruent results would be that patient characteristics moderate the impact of focus on performance.…”
Section: Discussioncontrasting
confidence: 99%
“…It would be unreasonable to assume that obesity surgery is on the extreme routine end of this scale, given that many obese patients have comorbidities that increase unpredictability and that many simpler elective procedures exist. However, we argue that the current standardized nature of the obesity surgery procedures means that patients undergoing obesity surgery can be characterized as relatively routine elective patients, and that this is a likely explanation of our results in relation to the results of Miedaner and Sülz [18].…”
Section: Discussionsupporting
confidence: 47%
See 3 more Smart Citations